Maternal attachment in their early childhood and in their motherhood at Child Psychiatric Out-patient Unit of King Chulalongkorn Memorial Hospital. - Kaewpoonsri, C.; Chandarasiri , P. (Chulalongkorn Medical Journal, 2023)
Background : The maternal attachment in their early childhood and in their motherhood that form the pattern of maternal cognition, emotion, behavior and interpersonal relationship via the experience of childhood attachment. There are fews researches on the continuation of maternal attachment in Thailand. Objective : To study the continuation of attachment from childhood to motherhood. Design : Qualitative research. Setting : Child Psychiatric Out-patient Unit of King Chulalongkorn Memorial Hospital Materials and Methods : Twelve mothers were recruited for qualitative research, the methods used in this study, also included literature review, an in-depth interview with semi-structured questionnaire of the Adult Attachment Interview. Data triangulation was used along with the content Analysis technique. Results : Most of the childhood attachments were insecure ambivalent attachment and secure attachment. All motherhood attachments were dismissing attachments. Conclusion : The study shows that childhood maternal attachment has developed from the experience of relationship with her parent such as parental sensitivity behavior, child-parental sensitivity experience. The attachment can be changed according to the age, the experience of losing attachment figure, lack of supervisor or other supporting systems, no sense of selfcoregulation or the experience of physical and sexual abuse in adolescence.